2018
DOI: 10.1200/po.17.00263
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity and Coexistence of T790M and T790 Wild-Type Resistant Subclones Drive Mixed Response to Third-Generation Epidermal Growth Factor Receptor Inhibitors in Lung Cancer

Abstract: Purpose Third-generation epidermal growth factor receptor (EGFR) inhibitors like nazartinib are active against EGFR mutation–positive lung cancers with T790M-mediated acquired resistance to initial anti-EGFR treatment, but some patients have mixed responses. Methods Multiple serial tumor and liquid biopsies were obtained from two patients before, during, and after treatment with nazartinib. Next-generation sequencing and droplet digital polymerase chain reaction were performed to assess heterogeneity and clo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
14
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 26 publications
3
14
0
Order By: Relevance
“…Whether molecular-targeting drugs are effective to tumors containing subclonal population harboring "actionable" mutations is an important question. As previous report 43,50,51 , our data showed that MB sequencing also detected PIK3CA, ERBB2 and KRAS subclonal mutations, which are linked to therapy response in various cancers. Thus, MB sequencing with Ion Ampliseq HD technology will be useful to detect subclonal mutations related to cancer therapy response.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Whether molecular-targeting drugs are effective to tumors containing subclonal population harboring "actionable" mutations is an important question. As previous report 43,50,51 , our data showed that MB sequencing also detected PIK3CA, ERBB2 and KRAS subclonal mutations, which are linked to therapy response in various cancers. Thus, MB sequencing with Ion Ampliseq HD technology will be useful to detect subclonal mutations related to cancer therapy response.…”
Section: Discussionsupporting
confidence: 85%
“…Several intrinsic or acquired rare variants in cancer have been identified that are associated with drug resistance. For instance, EGFR T790M and C797S and ALK L1196M mutations are associated with resistance to EGFR tyrosine kinase inhibitor and ALK inhibitors in non-small cell lung cancer, respectively [40][41][42][43] . Subpopulational KRAS activating mutations are associated with resistance to anti-EGFR therapy (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Genomic analysis of standard single-lesion tumor biopsies upon disease progression has been the mainstay of identifying mechanisms of acquired resistance, but recent studies suggest tumor biopsies may vastly under-represent the heterogeneity of resistance in a single patient 5,7,10,15,16 . In particular, analyzing a core biopsy from one region of a single metastatic lesion may fail to detect clinically-relevant resistance mechanisms, leading to mixed responses or failure of subsequent therapy 3,7,17 .…”
Section: Introductionmentioning
confidence: 99%
“…The diagnosis of a change in histology requires tissue assessment and cannot be achieved by ctDNA. Finally, we have observed significant heterogeneity of resistant EGFR ‐mutant lung cancers, highlighting the often complementary data afforded by both tissue and liquid biopsies . These factors emphasize the continued relevance and important role of tissue biopsies in this patient population and underline the importance of the current study, especially because osimertinib is now in the frontline setting and T790M is no longer the major finding of interest on molecular profiling.…”
Section: Discussionmentioning
confidence: 82%